Розсіювання поля діелектричного хвилеводу на призмі - Нєвров, В. Ю. (ХНУРЕ, 2021)
The field scattering of a dielectric waveguide by a prism is considered. The computer model is based on the use of the MEEP package. Formation of a wave beam in free space is shown for various material parameters of the system elements.
Keywords: ефект Черенкова; діелектрична призма; пакет МЕЕР